Clinical aspects and therapeutic approach of drug-induced adverse skin reactions in a quaternary hospital: a retrospective study with 219 cases - Júlia Chain Martins; Camila Arai Seque; Adriana Maria Porro (Sociedade Brasileira de Dermatologia, 2022)
Abstract Background Adverse drug reactions are frequent, with cutaneous manifestations being the most common. In the hospital environment, the incidence of cutaneous drug reactions varies from 2% to 3%. Objective To analyze the profile of cutaneous drug reactions, relating clinical forms, suspected medications, histopathological alterations, systemic repercussions, treatment and course. Methods Clinical, retrospective and observational study of patients seen by the Dermatology Interconsultation team from January 2013 to December 2016. Results The frequency of cutaneous drug reactions among the evaluated patients was 13.6%, with 219 cases diagnosed. In 65.7%, the reaction was considered mild, of which the most common was exanthema, while in 34.2%, the reaction was considered severe, with DRESS being the main form of reaction(18.2%). Antibiotics (36.5%) and anticonvulsants (10%) were the most involved drugs. In addition to drug discontinuation, systemic corticosteroids were prescribed in 47% of cases and intravenous immunoglobulin (IVIg) in 4.5%. Of the mild forms, in 62%, expectant management and/or exclusive use of symptomatic treatment was used. Study limitations Retrospective study, with limitations inherent to this type of investigation; lack of some information in medical records; long evaluation period, with a possible change in external validity. Conclusion The most frequently identified clinical form was exanthema, and antibiotics and anticonvulsants were the most frequently involved drug classes. About one-third of the patients had severe cutaneous drug reactions, with DRESS being the main one. Cutaneous drug reactions are frequent in clinical practice, and the dermatologist should be called in as soon as possible to assist in the diagnosis and management of these cases.